2010
DOI: 10.1038/npp.2009.224
|View full text |Cite
|
Sign up to set email alerts
|

Impulsivity Characterization in the Roman High- and Low-Avoidance Rat Strains: Behavioral and Neurochemical Differences

Abstract: The selective breeding of Roman high-(RHA) and low-avoidance (RLA) rats for rapid vs extremely poor acquisition of active avoidance behavior in a shuttle-box has generated two phenotypes with different emotional and motivational profiles. The phenotypic traits of the Roman rat lines/strains (outbred or inbred, respectively) include differences in sensation/novelty seeking, anxiety/fearfulness, stress responsivity, and susceptibility to addictive substances. We designed this study to characterize differences be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
107
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 134 publications
(130 citation statements)
references
References 75 publications
21
107
2
Order By: Relevance
“…Nevertheless, the present findings do show that these two behavioural traits can be dissociated in certain settings. Consistent with this view, Roman high-avoidance rats, which show less anxiety and reduced emotional reactivity to stressful stimuli compared with Roman low-avoidance rats (Escorihuela et al 1999), are reported to be more impulsive on both the 5-CSRTT and the delay-discounting task (Moreno et al 2010).…”
Section: Discussionmentioning
confidence: 89%
“…Nevertheless, the present findings do show that these two behavioural traits can be dissociated in certain settings. Consistent with this view, Roman high-avoidance rats, which show less anxiety and reduced emotional reactivity to stressful stimuli compared with Roman low-avoidance rats (Escorihuela et al 1999), are reported to be more impulsive on both the 5-CSRTT and the delay-discounting task (Moreno et al 2010).…”
Section: Discussionmentioning
confidence: 89%
“…Moreover, selective breeding for Roman high-(RHA) and low-avoidance (RLA) rats for rapid vs. extremely poor acquisition of active avoidance behavior in a shuttle box resulted in two phenotypes that included differences in sensation/novelty seeking, anxiety/fearfulness, stress responsivity, and susceptibility to addictive drugs (Driscoll et al 1998;Escorihuela et al 1997Escorihuela et al , 1999Fattore et al 2009). They also showed differences in two models of impulsivity, impulsive choice in delay discounting task and poor inhibitory control in 5-CSRTT, and in compulsivity in SIP acquisition and performance, with RHA manifesting impulsive-compulsive behavior (Moreno et al 2010). The characteristics that have been selected or bred in these different groups of rat strains did not point towards a specific common trait among them that could link with compulsive drinking.…”
Section: Behavioral Genetics and Strain Differencesmentioning
confidence: 91%
“…This excessive drinking, induced in food-deprived animals (80-85% from free feeding) and known as SIP, has been proposed as a prototype of adjunctive behavior and is unrelated to normal thirst or homeostatic needs, generally following an inverted-U-shaped pattern occurring immediately after the delivery of food (Falk 1961(Falk , 1971. Although different factors, such as the state of food deprivation or the interfood interval length reproduced by different fixed time (FT) or fixed interval (FI) schedules, influence the acquisition and expression of adjunctive drinking in SIP (Falk 1966a(Falk , 1971Flores and Pellón 1995;Flory 1971;Killeen 1970;López-Crespo et al 2004), data from our laboratory have shown that the optimal FT interval for inducing a high rate of drinking behavior is FT-30s (Cardona et al 2006) and FT-60s (López-Grancha et al 2006aMoreno et al 2010). The main variables measured during SIP are: (a) total amount of water (milliliters) removed from the bottle, (b) total number of licks, and (c) and total number of nose pokes in the food magazine.…”
Section: The Sip Proceduresmentioning
confidence: 92%
See 2 more Smart Citations